Postjournalism: essence, signs, social effects - Korochensky, Alexander P. (Journal of the Belarusian State University. Journalism, 2019)
The object of this research is the modern practices of media content formation that affect the characteristics of media texts and discourses, the subject is the radical transformation of modern journalism under the influence of the deepening commercialization of the media and the spread of new communication technologies. On the basis of theoretical analysis of contemporary media practices concluded the coexistence of journalism with the so-called postjournalism, generated by the activities with the other target attitudes and characteristics, that contrast with the mission and standards of traditional journalism. The article describes the features of postjournalism.